Preparation and Characterization of ZnO-Fe2O3 Nanocomposite Using Green Synthesis Method and Its Application in Powder Pyrotechnics - Lestariana, Evie; Supriyatno, Heru; Sitompul, Hamonangan Rekso Diputro; Restasari, Afni; Yulizar, Yoki (Science and Technology Indonesia, 2025)
Nanocomposites are often used as a catalyst in the pyrolysis of Al/Mg/KNO3 rocket igniter charge. Because the synthesis of the nanocomposites has a negative impact on the environment, in this study, the nanocomposite of ZnO-Fe2O3 was synthesized using a green synthesis method based on the aqueous fraction of Syzygium polyanthum (Wight) Walp. leaf extract. The secondary metabolites contained in the extract were tested. ZnO-Fe2O3 nanocomposite was characterized using Ultra-Violet-Visible Diffuse Reflectance Spectroscopy (UV Vis-DRS), Fourier Transform Infra-Red Spectroscopy (FT-IR), X-ray Diffraction (XRD), Particle Size Analyzer (PSA), Scanning Electron Microscope-Energy Dispersive X-Ray Spectroscopy (SEM-EDS), and Transmission Electron Microscope (TEM).The thermal decomposition process of Al/Mg/KNO3 with and without ZnO-Fe2O3 nanocomposite was analyzed using Differential Thermal Analysis (DTA) and Thermogravimetry Analysis (TGA). As a result, ZnO-Fe2O3 nanocomposite is successfully synthesized, proven by UV-Vis DRS, FT-IR, XRD, and SEM-EDS analysis. It highlights the effectiveness of aqueous leaves extract of Syzygium polyanthum (Wight) Walp. as a capping agent because of the secondary metabolites. Based on PSA and TEM characterization, the particle size is 17.37 nm. The TGA curves demonstrate that the addition of ZnO-Fe2O3 nanocomposite lowers the activation energy for decomposition of Al/Mg/KNO3, from 58.71 kJ/mol to 52.07 kJ/mol, as well as reduces the stage in the decomposition process. A particular reason lies on the role of ZnO-Fe2O3 nanocomposite in reducing the activation energy of the thermal decomposition ofKNO3.